2011
DOI: 10.1007/s11172-011-0067-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and study of gold nanoparticles stabilized by bioflavonoids

Abstract: A new procedure for the preparation of biocompatible gold nanoparticles using biofla vonoids: rutin, quercetin, and luteolin as reducing agents and stabilizers was proposed. On varying the bioflavonoid concentration, nanoparticles of different size are formed. By the combined use of spectroscopy and atomic force microscopy, the nanoparticle size was estimat ed (40-50 nm). Uniform and highly dispersed gold nanoparticles were obtained at Au : rutin ratios of 1 : 1, 2 : 1, and 4 : 1 and Au : quercetin ratios of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…Figure 2A(I) and Figure 2A(II) gives the FTIR spectra of cAuNps and free curcumin respectively along with their important bands. Sivaraman et al, and Levchenko et al, have reported the role of ionization of -OH groups of the flavonoids; tannic acid and rutin in the formation of AuNPs (Sivaraman et al, 2010;Levchenko et al, 2011). Likewise, it is confirmed from the FTIR data of cAuNPs that Au 3+ is being reduced as a result of enolic and phenolic -OH groups of curcumin.…”
Section: Synthesis and Characterization Of Curcumin Stabilized Gold Nmentioning
confidence: 92%
“…Figure 2A(I) and Figure 2A(II) gives the FTIR spectra of cAuNps and free curcumin respectively along with their important bands. Sivaraman et al, and Levchenko et al, have reported the role of ionization of -OH groups of the flavonoids; tannic acid and rutin in the formation of AuNPs (Sivaraman et al, 2010;Levchenko et al, 2011). Likewise, it is confirmed from the FTIR data of cAuNPs that Au 3+ is being reduced as a result of enolic and phenolic -OH groups of curcumin.…”
Section: Synthesis and Characterization Of Curcumin Stabilized Gold Nmentioning
confidence: 92%
“…Bio-active molecules such as luteolin, epigallocatechin gallate (EGCG), quercetin, rutin, curcumin etc. are shown to reduce gold salts and form stable AuNPs [9][10][11]. The anti-inflammatory and anti-oxidant activities of dietary flavonoids like fisetin, luteolin, quercetin, eriodictyol, baicalein and galangin, in various cell lines have been demonstrated [12][13][14][15].…”
Section: Introductionmentioning
confidence: 97%
“…48.25%-35.80% and 12.61%-15.80%, respectively. Significant increment in carbon and oxygen content directly suggest the attachment of polyphenolics on the surface of gold nanoparticles [6,40]. Si (10%) was present in both cases due to the glass slide base for the sample preparation.…”
Section: Resultsmentioning
confidence: 97%
“…Thus to reduce the side effects several biological methods are recently used to synthesise gold nanoparticles [5]. It is now well accepted that biological methods for nanoparticle synthesis using different plant extracts are eco-friendly and possible alternative of the generalised chemical methods and it also causes less toxic effects [5][6][7].…”
Section: Introductionmentioning
confidence: 99%